NUMERICAL SIMULATION OF THE MICROWAVE PASTEURIZATION PROCESS OF SOME FOOD LIQUIDS - Maria Miruna Unguroiu; Luca Valentin Alexa; Liviu Daniel Ghiculescu (Nonconventional Technologies Review)
The paper deals with numerical simulation by finite element method of microwave pasteurization process. The comparative study is focused on two liquids: milk and apples juice. Information regarding the state of the concerning the characteristics of pasteurization process and its dedicated installations are presented. The computerized results obtained from numerical simulation agree with experimental results from the state of the art, validating the models. These emphasize that microwave pasteurization process is very efficient in the removing the pathogen components in very short time, keeping the nutritive elements under conditions of industrial applicability.